(3eUHGM GdCfGe aj TQM TQGFY GdESdGe cJGH GdbQVs - (3GdfLaj, , GdHOjQj, GdHOjQj, LYaQ Hf CMeO Hf Sja, J (B1369(3g` (B1950(3es ((3HNW GdeDdas)
(3ChdgG (B:s
(3ChdgG(B: (3bhdg GdebUO GdNGeS aj GdbQV, Cbhd GYde Cf GdbQV eeG dG QjH ZjQ eTQhYjI Hjf GdESdGe adfTQ Edi HYV eG hQO ajg ef GdCNHGQ dJchf efgG Ydi HUjQIs
(3BNQgG (B:s
(3BNQgG(B: (3ef ZjQ NdGa ajg jYQa Hd QHeG (B.. (3GdNdGa ajg Hd dYdg eLeY Ydjg ceG ceG Yf HLeY GdHQgGf bdJ(B: (3hcja dj agPG gh GdPj jbJVjg bhGYO GdeOYh hGdefcQ ceG dG jNai (B. (3hGdMeO ddg QH GdYGdejfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B2: 121s
(3GdPQjYI, L (B21: 68s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis